The improved open-circuit voltage characterization test using active polarization voltage reduction method. (1st March 2019) - Yang, Jufeng; Huang, Wenxin; Xia, Bing; Mi, Chris
Highlights: Applied an extra current excitation to reduce polarization voltage. Analyzed parametric sensitivity of current excitation to model parameters. Developed a method to determine the parameters for the current excitation. Shortened the test time due to the active polarization voltage reduction. Validated the feasibility and superiority with experiments. Abstract: The correlation between state of charge (SoC) and open-circuit voltage (OCV) is a crucial characteristic parameter in many aspects of the battery management system (BMS). However, it is a challenging task to obtain the accurate SoC-OCV correlation with a high test efficiency. In this paper, an improved OCV characterization test is proposed to actively reduce the polarization voltage. Based on the third-order equivalent circuit model (ECM), two sets of current pulses are applied to accelerate the convergence of the battery terminal voltage, thus the test time is effectively shortened compared to the conventional incremental OCV characterization test. Furthermore, the parametric sensitivity of the imposed current excitation to battery model parameters is analyzed. Subsequently, the parametric determination method for the imposed current excitation is provided. Experiments are conducted on a lithium-ion polymer battery to prove the feasibility of the proposed test procedure. Comparison with the conventional OCV characterization test further demonstrated the superiority of the proposed test procedure.